The pros and cons of nucleic acid-amplified immunoassays-a comparative study on the quantitation of prostate-specific antigen with and without rolling circle amplification - Dekaliuk, Mariia; Farka, Zdeněk; Hildebrandt, Niko (Analytical and bioanalytical chemistry, 2024)
Integrating isothermal nucleic acid amplification strategies into immunoassays can significantly decrease analytical limits of detection (LODs). On the other hand, an amplification step adds time, complication, reagents, and costs to the assay format. To evaluate the pros and cons in the context of heterogeneous multistep immunoassays, we quantified prostate-specific antigen (PSA) with and without rolling circle amplification (RCA). In addition, we compared time-gated (TG) with continuous-wave (CW) photoluminescence (PL) detection using a terbium complex and a fluorescein dye, respectively. For both direct (non-amplified) and amplified assays, TG PL detection provided circa four- to eightfold lower LODs, illustrating the importance of autofluorescence background suppression even for multi-wash assay formats. Amplified assays required an approximately 2.4 h longer assay time but led to almost 100-fold lower LODs down to 1.3 pg/mL of PSA. Implementation of TG-FRET (using a Tb-Cy5.5 donor-acceptor pair) into the RCA immunoassay resulted in a slightly higher LOD (3.0 pg/mL), but the ratiometric detection format provided important benefits, such as higher reproducibility, lower standard deviations, and multiplexing capability. Overall, our direct comparison demonstrated the importance of biological background suppression even in heterogeneous assays and the potential of using isothermal RCA for strongly decreasing analytical LODs, making such assays viable alternatives to conventional enzyme-linked immunosorbent assays (ELISAs).
Keywords: lidé; PSA; Nucleic Acid Amplification Techniques; Diagnostics; prostatický specifický antigen; ELISA; techniky amplifikace nukleových kyselin; Humans; imunoanalýza; Immunoassay; Fluorescence Resonance Energy Transfer; mužské pohlaví; Prostate-Specific Antigen; Limit of Detection; rezonanční přenos fluorescenční energie; Fluorescence; limita detekce; Terbium; Male; TR-FRET